2018
DOI: 10.1111/aos.13662
|View full text |Cite
|
Sign up to set email alerts
|

The relation between dietary intake and glaucoma: a systematic review

Abstract: Intake of selenium and iron may increase the risk of glaucoma, though, only few studies have been done on this topic. Nitric oxide present in other dark green leafy vegetables seems to have a beneficial effect on glaucoma. However, the evidence for an association of dietary intake with glaucoma is still not strong. More (longitudinal and randomized clinical trials) studies are required to make the presented findings clinically applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 67 publications
1
36
0
3
Order By: Relevance
“…Kant et al [ 39 ] used a food frequency questionnaire to assess the relation between the intake of a variety of antioxidants derived from food and dietary supplements in 474 glaucoma patients selected from the Nurses' Health Study and the Health Professionals Follow-up Study and followed for more than 10 years and did not observe any strong associations between antioxidant consumption and the risk of primary open-angle glaucoma. In a systematic review of 46 articles in which the effect of nutrients on open-angle glaucoma was studied, nitric oxide present in dark green leafy vegetables seemed to have a beneficial effect [ 27 ]. Interestingly, Wang et al [ 26 ] analyzed the association between glaucoma and daily intake of PUFAs, including ω -3 fatty acids, in 3865 participants in the National Health and Nutrition Examination Survey 2005–2008 database who were 40 years or older and has available results of eye examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kant et al [ 39 ] used a food frequency questionnaire to assess the relation between the intake of a variety of antioxidants derived from food and dietary supplements in 474 glaucoma patients selected from the Nurses' Health Study and the Health Professionals Follow-up Study and followed for more than 10 years and did not observe any strong associations between antioxidant consumption and the risk of primary open-angle glaucoma. In a systematic review of 46 articles in which the effect of nutrients on open-angle glaucoma was studied, nitric oxide present in dark green leafy vegetables seemed to have a beneficial effect [ 27 ]. Interestingly, Wang et al [ 26 ] analyzed the association between glaucoma and daily intake of PUFAs, including ω -3 fatty acids, in 3865 participants in the National Health and Nutrition Examination Survey 2005–2008 database who were 40 years or older and has available results of eye examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dietary consumption of PUFAs in glaucoma has been proposed as a modifiable factor for IOP regulation through docosanoids-driven increase of aqueous outflow [ 22 ], reversal of ω -3 and ω -6 imbalance in red blood cell membranes [ 23 , 24 ], and improvement of glaucomatous optic neuropathy [ 25 ]. However, the clinical experience with dietary intake of ω -3 PUFAs in glaucoma is very limited [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predominant risk factor for glaucoma is age, and there is not yet a well-established nutrient or food association with glaucoma and a very small number of studies have rigorously tested dietary patterns as risk factors for glaucoma. A systematic review found that some micronutrients like selenium and iron may be associated with increased risk for glaucoma, while components of dark-green leafy vegetables, specifically glutathione, flavonoids, and nitric oxide, were significantly associated with decreased risk for glaucoma [ 36 ]. The disparate effects of nutrients that synergize within a given dietary pattern may explain the lack of clear associations between dietary patterns and glaucoma.…”
Section: Dietary Patterns and Eye Diseasementioning
confidence: 99%
“…Participants who met the following criteria in both eyes served as controls: (1) IOP �21 mmHg, (2) presence of an open angle (PACD >1/4 corneal thickness), (3) non-glaucomatous optic disc (vertical and horizontal CDR <0.7 and inter-eye difference of vertical and horizontal CDR <0.2), (4) absence of DH or RNFL defect, and (5) optic disc not violating the ISNT rule.…”
Section: Plos Onementioning
confidence: 99%
“…However, it is also true that glaucoma development or progression can occur even if the IOP is within the normal range. Many studies have been conducted to identify other solutions for patients who cannot be managed by lowering IOP [1,2]. In addition to this, various other risk factors affecting glaucoma have been reported [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%